2020
DOI: 10.5946/ce.2019.118
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Yield, Appropriateness, and Complications of Pediatric Upper Gastrointestinal Endoscopy in an Adult Suite: A Retrospective Study of 822 Children

Abstract: Background/Aims: This study aimed to study the endoscopic yield, appropriateness, and complications of pediatric endoscopy performed by adult gastroenterologists in an adult endoscopic suite. Methods: This a retrospective study in which records of all the patients less than 18 years of age who underwent endoscopy in the last 5 years were studied. The indications of endoscopy in children were categorized as appropriate or inappropriate per the latest guidelines by American Society for Gastrointestinal Endoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…In this issue of Clinical Endoscopy, Wani et al demonstrated that pediatric endoscopy for children over 4 months of age was safely performed by adult gastroenterologists in conjunction with a pediatrician. 6 This finding is supportable in most of the countries where pediatric endoscopists are few. Furthermore, acknowledging the presence of a pediatric gastroenterologist, the collaboration of an adult gastroenterologist is vital for the optimal management of pediatric patients because adult endoscopists are capable of performing more complex endoscopic procedures (e.g., endoscopic retrograde cholangiopancreatography, endoscopic ultrasonography, and stent placement).…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…In this issue of Clinical Endoscopy, Wani et al demonstrated that pediatric endoscopy for children over 4 months of age was safely performed by adult gastroenterologists in conjunction with a pediatrician. 6 This finding is supportable in most of the countries where pediatric endoscopists are few. Furthermore, acknowledging the presence of a pediatric gastroenterologist, the collaboration of an adult gastroenterologist is vital for the optimal management of pediatric patients because adult endoscopists are capable of performing more complex endoscopic procedures (e.g., endoscopic retrograde cholangiopancreatography, endoscopic ultrasonography, and stent placement).…”
mentioning
confidence: 63%
“…Authors from Kashmir, India, had reported 110 pediatric cases of therapeutic endoscopy (e.g., active bleeding control, variceal ligation, foreign body removal, etc.). 6 To comment from the standpoint of a pediatric gastroenterologist, I have some tips based on my experience and the Internet. Endoscopic variceal ligation (EVL) is often required for infants with advanced liver cirrhosis because of biliary atresia awaiting liver transplantation.…”
mentioning
confidence: 99%
See 3 more Smart Citations